Title of Article- Comparative Evaluation of Novabone Putty In Combination With Platelet Rich Fibrin (PRF) And Platelet Rich Fibrin (PRF) Alone In The Treatment of Human Infrabony Defects– A Randomized Clinical Trial - Agrawal, Diksha; Jaiswal, Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
Periodontitis is chronic inflammatory disease leads to loss of supporting structures of the teeth results in exfoliation of teeth.(1, 2) Treatment of these periodontal condition is mandatory. Previously, decreasing the disease advancement considered as utmost treatment protocol by preserving the lost periodontal structures.(3,4)